The effects of litter input and increased precipitation on soil microbial communities in a temperate grassland - Gao, Xiuli; Zheng, Zhirong; Diao, Zhaoyan; Zhang, Yeming; Wang, Yupei; Ma, Linna (Frontiers in Microbiology, 2024)
Global warming has contributed to shifts in precipitation patterns and increased plant productivity, resulting in a significant increase in litter input into the soils. The enhanced litter input, combined with higher levels of precipitation, may potentially affect soil microbial communities. This study aims to investigate the effects of litter input and increased precipitation on soil microbial biomass, community structure, and diversity in a temperate meadow steppe in northeastern China. Different levels of litter input (0%, +30%, +60%) and increased precipitation (0%, +15%, +30%) were applied over a three-year period (2015-2017). The results showed that litter input significantly increased the biomass of bacteria and fungi without altering their diversity, as well as the ratio of bacterial to fungal biomass. Increased precipitation did not have a notable effect on the biomass and diversity of bacteria and fungi, but it did increase the fungal-to-bacterial biomass ratio. However, when litter input and increased precipitation interacted, bacterial diversity significantly increased while the fungal-to-bacterial biomass ratio remained unchanged. These findings indicate that the projected increases in litter and precipitation would have a substantial impact on soil microbial communities. In energy- and water-limited temperate grasslands, the additional litter inputs and increased precipitation contribute to enhanced nutrient and water availability, which in turn promotes microbial growth and leads to shifts in community structure and diversity.